2017
DOI: 10.1038/srep40031
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of predisposing genetic factors for DiGeorge/velocardiofacial syndrome

Abstract: DiGeorge/velocardiofacial syndrome (DGS/VCFS) is a disorder caused by a 22q11.2 deletion mediated by non-allelic homologous recombination (NAHR) between low-copy repeats (LCRs). We have evaluated the role of LCR22 genomic architecture and PRDM9 variants as DGS/VCFS predisposing factors. We applied FISH using fosmid probes on chromatin fibers to analyze the number of tandem repeat blocks in LCR22 in two DGS/VCFS fathers-of-origin with proven 22q11.2 NAHR susceptibility. Results revealed copy number variations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This includes a large inversion polymorphism encompassing one of the most common rearrangements associated with autism at chromosome 16p11.2 and one of the most frequent deletions in the human population at the DiGeorge/VCF syndrome critical region (Additional file 1 : Fig. S18) [ 20 , 21 ]. We further investigate the Cooper syndrome region on chromosome 15q25.2 using available HPRC assemblies and define eight structurally diverse haplotypes with various frequencies in human populations.…”
Section: Resultsmentioning
confidence: 99%
“…This includes a large inversion polymorphism encompassing one of the most common rearrangements associated with autism at chromosome 16p11.2 and one of the most frequent deletions in the human population at the DiGeorge/VCF syndrome critical region (Additional file 1 : Fig. S18) [ 20 , 21 ]. We further investigate the Cooper syndrome region on chromosome 15q25.2 using available HPRC assemblies and define eight structurally diverse haplotypes with various frequencies in human populations.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, all but one of these rare inversion polymorphisms overlap a pathogenic copy number variant in the human population, strengthening our recent observation of disease association (Porubsky, Höps, et al 2022). This includes a large inversion polymorphism encompassing one of the most common rearrangements associated with autism at chromosome 16p11.2, which maps to the DiGeorge/VCF syndrome critical region interval that has been extensively studied (Gebhardt et al 2003; Vergés et al 2017) and a multi-Mbp inversion corresponding to the Cooper syndrome region on chromosome 15q25.2. Using the HPRC assemblies ( Data availability ), we define eight structurally diverse haplotypes with various frequencies in human populations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Table S31 and S32). It is reasonable to assume that features present in addition to PRDM9‐binding sites, such as structural variants (CNVs) of the recombining paralogs or chromatin accessibility, can also influence NAHR frequency (Antonacci et al., ; Carvalho & Lupski, ; Cuscó et al., ; Vergés, Molina, Geán, Vidal, & Blanco, , ). Polymorphic large inversions present in the transmitting parents have been identified that predispose to NAHR‐mediated rearrangements involving a number of different human genes (Antonacci et al., ; Bayés, Magano, Rivera, Flores, & Pérez Jurado, ; Gimelli et al., ; Hobart et al., ; Koolen et al., ; Molina, Anton, Vidal, & Blanco, ; Osborne et al., ; Scherer et al., ; Sharp et al., ; Small, Iber, & Warren, ; Visser et al., ).…”
Section: Discussionmentioning
confidence: 99%